Clownsmasken im Film: Wie Maskierungen kulturelle Ängste enthüllen - Augustin, Yvonne (transcript, 2018)
Clown characters have always played a decisive role when depicting social conflicts: Wearing their masks, they embody and reveal cultural anxieties.